Expression of c-myc and bcl-2 oncogene products in Reed-Sternberg cells independent of presence of Epstein-Barr virus. Issue 3 (March 1993) - Jiwa, N M; Kanavaros, P; van der Valk, P; Walboomers, J M; Horstman, A; Vos, W; Mullink, H; Meijer, C J
Abstract : AIMS: To evaluate the expression of c-myc and bcl-2 oncogene products in Reed-Sternberg cells in Hodgkin's disease, especially in relation to Epstein-Barr virus infection and expression of EBV encoded latent membrane protein (LMP). METHODS: Tissues from 33 cases of Hodgkin's disease were studied for the presence of EBV DNA by polymerase chain reaction (PCR) and DNA in situ hybridisation (DISH), for the presence of EBER-1 and EBER-2 EBV RNA by RNA in situ hybridisation (RISH); and for the presence of LMP, bcl-2, and c-myc proteins by immunohistochemical staining. RESULTS: A substantial number of Reed-Sternberg cells expressed bcl-2 in 20 of 29 (69%) and c-myc in 30 of 32 (94%) Hodgkin's disease samples. In 18 of the 25 (72%) cases Reed-Sternberg cells expressed both oncogene products. Of these 18 cases, 10 (56%) were EBV-PCR positive; eight (44%) were EBV-PCR negative. CONCLUSIONS: Reed-Sternberg cells in Hodgkin's disease frequently express both bcl-2 and c-myc oncogene products, suggesting that these oncogenes may act in concert in the pathogenesis of the disease. Moreover, the expression of c-myc and bcl-2 proteins in Reed-Sternberg cells is independent of EBV and LMP status.